Analysis of causes of acute peripheral vascular lesion in neonates and individualized surgical treatment and nursing (新生儿急性外周血管病损的原因分析及外科治疗和个性化护理) - MA Lijuan (马丽娟); CHENG Lili (程丽丽); XIE LI (谢丽) (中西医结合护理, 2022)
This paper reviewed the clinical data of 5 newborn infants with acute peripheral vascular lesion, and summarized individualized surgical treatment and nursing management. The types of peripheral vascular lesion included mural thrombus at initiation site of left external iliac vein in 2 cases, false aortic aneurysm of posterior tibial of left leg in 1 case, thrombophlebitis of left leg in 1 case, false aortic aneurysm of at left elbow in 1 case. Based on the analysis of cause analysis, implementation of individualized surgical treatment and nursing strategy may achieve good clinical outcomes in the treatment of acute peripheral vascular lesion in neonates. (回顾性分析医院2015年10月—2022年10月收治的5例外周血管病损的新生儿临床护理资料, 分析发病原因, 总结护理经验。5例新生儿外周血管病损类别: 左髂外静脉起始部完全性附壁血栓2例, 左小腿胫后动脉假性动脉瘤1例, 右小腿血栓性静脉炎1例, 左肘部肱动脉假性动脉瘤1例。对于新生儿外周血管病损, 在治疗及护理过程中, 针对不同的病因造成的病损, 应采取个性化治疗护理进行干预, 取得较好的结局。)